Diltiazem prevents monosodium glutamate toxicity on testes in rats - Bojanić, Vladmila; Najman, Stevo; Veličkov, Aleksandra; Bojanić, Novica; Milenković, Jelena (Acta medicae Medianae, 2020)
Diltiazem prevents monosodium glutamate toxicity on testes in ratsAbstractIncreased exposure to food additives may exhibit harmful effect on male reproductive system. Neonatal application of high doses of popular taste enhancer monosodium glutamate (MSG) to different kinds of animals cause lesions of the hypothalamic nuclei and the retina. Later in adulthood, animals exhibit a series of neuroendocrine disorders (stunted growth, obesity and decreased fertility).The mechanism of MSG action is not completely explained yet. We hypothesized that high concentration of MSG could alter permeability of neural membrane for calcium. The objective of our study is to find out could pretreatment with diltiazem, a calcium channel blocker, prevent harmful effect of MSG on testes in rats. Male rat pups treated with: 0.9% sodium chloride (C group), 4 mg/g BW of MSG (M group), 5 mg/g BW of diltiazem (D group) and diltiazem 5 mg/g BW with MSG (DM group) on 2nd,4th,6 th,8 th,10 th postnatal day. Animals were sacrificed at age of six months. MSG treatment resulted in: stunted growth (decreased naso-anal length and tail length; p
Keywords: Key words: monosodium glutamate, diltiazem, morphometric parameters, testes, toxicity